Analysis of Compensation and Employment Status in Reducing Nurse Turnover Intention in Hospitals - Nova Yasita; Dasrun Hidayat; Mira Veranita (Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2026)
This study aims to analyze the effect of performance allowances, employment status, and old age security on the turnover intention of nurses at Kharitas Bhakti Private Hospital, Pontianak. This study is motivated by the fact that high nurse turnover can have a negative impact and pose a serious challenge to the efficiency and effectiveness of healthcare services. Turnover can impact staffing, as increased turnover increases the workload due to caring for more patients than usual. To address this issue, this study used a quantitative approach with an analytical survey method and a cross-sectional approach. The results showed that performance allowances had an effect on nurses' turnover intention. Performance allowances were shown to have a negative relationship and influence on nurses' turnover intention. There was an effect of old age security on nurses' turnover intention. Old age security was shown to have a relationship and influence on nurses' turnover intention. Employment status was shown to have a relationship and influence on nurses' turnover intention. Nurse turnover intention at Kharitas Bhakti Private Hospital. It is expected that the hospital will improve the quality of performance allowances, provide certainty regarding employee status, and strengthen the old-age security program as strategic steps to reduce nurse turnover intention.